Federalism and Regionalism in Australia: New Approaches, New Institutions? - Brown, A.J (ANU Press, 2007)
Australia's federal system is in a state of flux and its relevance is being challenged. Dramatic shifts are occurring in the ways in which power and responsibility are shared between governments. Pressure for reform is coming not just from above, but from below, as the needs of local and regional communities - both rural and urban - occupy an increasingly important place on the national stage. How will these competing pressures for centralisation and devolution in the structures of federalism be reconciled? In this volume, experts and policy practitioners from diverse backgrounds canvass this uncertain future to conclude that the future of state, regional and local institutions is not only a vital question of federal governance, but must be addressed in a conscious and concerted way if Australian federalism is to evolve in ways that are sufficiently legitimate, effective, efficient and adaptive.